NITROGEN USE EFFICIENCY: A LOCAL AND REGIONAL APPROACH FOR BRAZILIAN AGRICULTURE - Tôsto, Karina Lima; Pacheco, Felipe Siqueira; Gomes, Luciene; Miranda, Marcela; Oliveira, Simoni Maria Loverde; Pessi, Dhonatan Diego; Cox, Christopher; Ometto, Jean Pierre Henry Balbaud (Ra’e Ga: o Espaço Geográfico em Análise, 2019)
The exponential growth of human activities has been significantly altering the global Nitrogen (N) cycling. Due to the scale of these changes, integrated approaches are required to optimize nutrient cycles to meet food and energy demands, while minimizing threats to climate, ecosystem services, and human health. Brazil is now in a leading position on the world stage as one of the great producers and exporters of agricultural products, and must reconcile the expansion of this sector with environmental preservation and promotion of social equity. The Nitrogen Use Efficiency (NUE) is a tool to evaluate the progress of its management, and can be estimated by the ratio between the outflows and N inputs in the agro systems. In this study, NUE was calculated on different scales: regional, covering the entire Brazilian territory, and local, comprising the Vermelho River watershed, an important agricultural area of the Upper Pantanal. The spatialized results indicate great heterogeneity in the NUE, with most of the Brazilian states presenting values outside the desirable range. Low efficiency in nutrient use is identified in several states of Northeast and Southeastern Brazil. On the other hand, regions of great agricultural importance in the Cerrado have high values, suggesting that the N exports by the products outweigh the replacement of this element, which can lead to N mining and degradation of productive land. On a local scale, NUE is very close to the desirable ceiling, with subtle reduction between 2000 and 2015.